Study of the mobility of trace elements at the water-sediment interface in coastal and estuarine areas - Diop, Cheikh; Ouddane, Baghdad (Revue des Sciences de l’Eau / Journal of Water Science, 2020)
In coastal and estuarine environments, trace elements trapped in sediments can be released back into the water column if resuspended during tides or floods. This is how this work is carried out to determine the mobility of trace elements when these phenomena occur on Senegalese coasts subjected to high energy tides. Sequential extraction carried out according to the European Community Bureau of Reference (BCR) was used to determine the mobilizable fraction of trace elements in sediments. Subsequently, laboratory sediment resuspension experiments were conducted to evaluate the ability of sediments to release trace elements into the water in order to better understand the natural effect of resuspension during tidal cycles and water movement on the coast. The release of elements into the water was monitored over a 24 h period along with redox potential (Eh), dissolved oxygen and pH. Bioavailability percentages of Cd, Ni, Pb and Zn showed a strong affinity with the acid soluble fraction, suggesting easy mobility of these elements. The results of the kinetic monitoring tests of the release of trace elements in water show that during the first minutes, desorption is very important with peaks that can reach 90‰ depending on the element that could potentially cause acute effects on aquatic organisms. However, the bioavailability of trace elements in contaminated sediments only influences mobility at the beginning of resuspension. Remobilization tests would therefore provide an indication of the ability of sediments to release trace elements during rapid changes in the physico-chemical conditions of the aquatic environment.